Ivabradine versus bisoprolol in the treatment of inappropriate sinus tachycardia: a long-term follow-up study. Issue 12 (December 2021) - Martino, Annamaria; Rebecchi, Marco; Sette, Antonella; Cicogna, Francesco; Politano, Alessandro; Sgueglia, Marianna; de Ruvo, Ermenegildo; Volterrani, Maurizio; Calo', Leonardo
Abstract : Aim: The aim of our study was to compare ivabradine versus bisoprolol in the short-term and long-term treatment of inappropriate sinus tachycardia. Methods: From this prospective, parallel-group, open-label study, consecutive patients affected by inappropriate sinus tachycardia received ivabradine or bisoprolol and were evaluated with Holter ECG, ECG stress test, European Heart Rhythm Association score and Minnesota Living With Heart Failure Questionnaire at baseline, after 3 and 24 months. Results: Overall, 40 patients were enrolled. Baseline parameters were comparable in the ivabradine and bisoprolol subgroups. Two patients had transient phosphenes with ivabradine and two others interrupted the drug after 3 months as they planned to become pregnant. Eight individuals treated with bisoprolol experienced hypotension and weakness, which caused drug discontinuation in five of them. Ivabradine was superior to bisoprolol in reducing Holter ECG mean heart rate (HR) and mean HR during daytime at short- and long-term follow-up. Moreover, ivabradine but not bisoprolol significantly reduced Holter ECG mean HR during night-time as well as maximal and minimal HR and significantly increased the time duration and maximal load reached at ECG stress test. The quality of life questionnaires significantly improved in both subgroups. Conclusion: This study suggests that ivabradine is better tolerated than bisoprolol and seems to be superior in controlling the heart rate and improving exercise capacity in a small population of individuals affected by inappropriate sinus tachycardia during a short-term and long-term follow-up.